De novo transcriptome assembly and the putative biosynthetic pathway of steroidal sapogenins of Dioscorea composita. - Xia Wang; Dijia Chen; Yuqi Wang; Jun Xie (PLoS ONE, 2015)
The plant Dioscorea composita has important applications in the medical and energy industries, and can be used for the extraction of steroidal sapogenins (important raw materials for the synthesis of steroidal drugs) and bioethanol production. However, little is known at the genetic level about how sapogenins are biosynthesized in this plant. Using Illumina deep sequencing, 62,341 unigenes were obtained by assembling its transcriptome, and 27,720 unigenes were annotated. Of these, 8,022 unigenes were mapped to 243 specific pathways, and 531 unigenes were identified to be involved in 24 secondary metabolic pathways. 35 enzymes, which were encoded by 79 unigenes, were related to the biosynthesis of steroidal sapogenins in this transcriptome database, covering almost all the nodes in the steroidal pathway. The results of real-time PCR experiments on ten related transcripts (HMGR, MK, SQLE, FPPS, DXS, CAS, HMED, CYP51, DHCR7, and DHCR24) indicated that sapogenins were mainly biosynthesized by the mevalonate pathway. The expression of these ten transcripts in the tuber and leaves was found to be much higher than in the stem. Also, expression in the shoots was low. The nucleotide and protein sequences and conserved domains of four related genes (HMGR, CAS, SQS, and SMT1) were highly conserved between D. composita and D. zingiberensis; but expression of these four genes is greater in D. composita. However, there is no expression of these key enzymes in potato and no steroidal sapogenins are synthesized.